Prevalence and correlates of Campylobacter and Salmonella species in small-scale broiler poultry, Gauteng, South Africa, 2020-2021 - Amar, Shira Rebeka (My University, 2022)
Background Campylobacter spp. and non-typhoidal Salmonella enterica (NT S. enterica) serovars are commonly isolated zoonotic bacteria associated with foodborne disease in humans. Colonisation of broilers with these pathogens compromises food safety for consumers of poultry products. Prevalence estimates of Campylobacter spp. and NT S. enterica serovars in local small-scale broiler production systems are sparse. Furthermore, biosecurity measures practiced in these production systems are not documented. This study aimed to estimate the prevalence of Campylobacter spp. and NT S. enterica serovars among small-scale broilers and examine the correlation of biosecurity practices with Campylobacter spp. positivity in Gauteng Province, South Africa. Methods Secondary cross-sectional data from a survey of 30 small-scale broiler farms was analysed. Farmers completed a farm management and biosecurity questionnaire. Cloacal swabs from 900 broilers were cultured using standard methods for Campylobacter spp. and Salmonella. Isolates were identified using a real-time polymerase chain reaction test. Farm and bird-level prevalence was calculated. Biosecurity correlates of Campylobacter spp. were identified using univariable and multivariable logistic regression while accounting for clustering of broilers by farm. Potential confounders such as season, antibiotic use and age at slaughter were adjusted for. Results NT S. enterica serovars were not isolated (0% (0/900), 95% CI (0.0– 4.0%)). In contrast, Campylobacter spp. were detected in 49.8% of broilers (448/900, 95% CI (46.5–53.1%)) with an overall farm prevalence of 90% (27/30, 95% CI (73.4–97.9%)). Campylobacter coli was dominant (65.4%, 316/483) over C. jejuni (34.6%, 167/483). Among sampled broiler farms, 53.3% (16/30) applied rodent control methods and 56.7% (17/30) used soap and disinfectant for poultry house hygiene. Exposures correlated to Campylobacter spp. positivity included open-walled naturally ventilated houses compared to free-range housing (OR= 3.82 95% CI (2.09 – 6.97)), drinking water treatment (OR=86.81 95% CI (4.56 – 1651.50)) and unsealed feed bags or feed spillage (OR= 12.48, 95% CI (2.88 – 54.12)). Conversely, the summer season (OR=0.06, 95% CI (0.02–0.20)) was protective. Conclusion Campylobacterspp. were highly prevalent in sampled broilers while no NT S. enterica serovars were isolated. Appropriate drinking water treatment and correct feed management of highquality feed and improved hygiene of poultry houses emerged as important biosecurity and farm management practices that may reduce the odds of Campylobacter spp. positivity in small-scale production systems. These findings may be used to improve the health of broilers produced in small-scale systems and promote food safety for consumers in this market sector.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science (Epidemiology) to the Faculty of Health Sciences, School of Public Health University of the Witwatersrand, Johannesburg, 2022